Planck 2013 results: XXIX. The Planck catalogue of Sunyaev-Zeldovich sources : Addendum - Ade, Peter A.; Bartelmann, Matthias (Arxiv, 2015)
We update the all-sky Planck catalogue of 1227 clusters and cluster candidates (PSZ1) published in March 2013, derived from Sunyaev-Zeldovich (SZ) effect detections using the first 15.5 months of Planck satellite observations. Addendum. We deliver an updated version of the PSZ1 catalogue, reporting the further confirmation of 86 Planck-discovered clusters. In total, the PSZ1 now contains 947 confirmed clusters, of which 214 were confirmed as newly discovered clusters through follow-up observations undertaken by the Planck Collaboration. The updated PSZ1 contains redshifts for 913 systems, of which 736 (~80.6%) are spectroscopic, and associated mass estimates derived from the Y_z mass proxy. We also provide a new SZ quality flag, derived from a novel artificial neural network classification of the SZ signal, for the remaining 280 candidates. Based on this assessment, the purity of the updated PSZ1 catalogue is estimated to be 94%. In this release, we provide the full updated catalogue and an additional readme file with further information on the Planck SZ detections.